Biochemical Iindexes of Tissues in Some Commercial Fish Speies at the Zaporizke Reservoir (Ukraine) - Ananieva, Tamila; Fedonenko, Elena (Agrobiodiversity for Improving Nutrition, Health and Life Quality, 2017)
The purpose of the work was to study the ecological and physiological state of the industrial ichthyofauna of the Zaporizke Reservoir on the basis of biochemical analysis of tissues and organs of fish with different types of nutrition and habitat in modern conditions. The indexes of protein, total lipids, and glycogen contents had been determined in the main commercial fish species from two sections of the Zaporizke Reservoir (Ukraine) with different contamination levels. The research was conducted using the muscle, liver and gills tissue samples from pike-perch (Sander lucioperca L.), European perch (Perca fluviatilis L.), bream (Abramis brama L.), and roach (Rutilus rutilus L.). Subjects were selected by standard methods of research control catches at the lower section of the Zaporizke Reservoir area near the Viyskove village (48° 22‘ 30.75“ N; 35° 20‘ 80.05 “E), which is characterized by environmental conditions as “conventionally clean”, and Samara Bay (48° 53‘ 40.21“ N; 35° 18‘ 73.20“ E) as technogenically contaminated zone. In predatory fish in the muscles and liver tissue there were the higher protein contents, due to the peculiarities of their nutrition. The processes of carbohydrate and lipid metabolism were most susceptible to deterioration of the environment, as it was evidenced by a statistically significant (p ≤0.05) reduction in the contents of both glycogen and total lipids in the liver tissues in fish from the “contaminated” zone of the reservoir. Violations of plastic and energy exchange were exposed, that they had a chronic character. Obtained data could be used for estimation of food quality of the explored industrial-valuable fishes of the reservoir, and for the diagnostic prognoses of the ecological and physiological state of fish populations under the conditions of anthropogenic loading.